(untitled) (RENTAS: Jurnal Bahasa, Sastera dan Budaya, 2022)
The development of social media in Indonesia has increased sharply and is marked by the use of social media by almost half of Indonesia’s population. One of the social media that Indonesians are interested in is Instagram. On Instagram, users can carry out social, economic, cultural, and language interactions. Thus, it is significant to study language interactions used to mark the emotional expression of speakers through the use of curses. The present study is entitled “Expression of Emotion as Impoliteness Markers in Instagram Comments Section in Indonesia: A Pragmatic Study”. The study aims to describe the form, reference, and impact of using emotional expressions as impoliteness markers. The meaning of the emotional expression in this study is limited to the use of swear words on three popular Instagram accounts in Indonesia. This study used the descriptive qualitative method. Data were collected using observation and note-taking techniques and then classified based on form, reference, and impoliteness. The theory used in this research is the theory of the form and reference of swear words in Indonesian developed by Wijana (2004) and the theory of impoliteness by Culpeper (2008). Based on the results of the study, it is known that the swear words in the Instagram accounts which are used based on their form consist of words, phrases, and clauses. The references of swear words that appeared include characteristics/conditions, animals, objects, body parts, spirits, activities, and professions. The form and reference to the curse words mark (a) positive impoliteness, (b) negative impoliteness, and (c) sarcasm or pseudo-politeness. These three forms of impoliteness occurred because what the speakers said contradicted what was considered by the interlocutors, and what was stated by the speakers was considered to violate the cultural norms/values ​​that exist in Indonesia, so the interlocutor resorted to scolding to express their emotional expressions. The research findings can be used to understand the culture of how Indonesians express their thought and feeling on social media. Furthermore, the research contributes to increasing literacy of language politeness in social media.